Genetic structure of the South European toothcarp Aphanius fasciatus (Actinopterygii: Cyprinodontidae) populations in the Mediterranean basin with a focus on the Venice lagoon. Issue 1 (1st January 2017) - Cavraro, F.; Malavasi, S.; Torricelli, P.; Gkenas, C.; Liousia, V.; Leonardos, I.; Kappas, I.; Abatzopoulos, T. J.; Triantafyllidis, A.
ABSTRACT: The genetic structure of Aphanius fasciatus populations has been analysed using two mitochondrial DNA (mtDNA) markers (16S rRNA and D-loop) obtained from specimens collected in nine sites from the Venice lagoon, Comacchio saltworks and Corsica. Available GenBank sequences were also included, in order to extend the results on a Mediterranean scale. Genetic polymorphism within the Venice lagoon was very low, with most of the specimens analysed (66% for 16S rRNA and 83% for D-loop) sharing the same haplotype for either of the two markers. The genetic homogeneity found within the Venice lagoon may be the consequence of the northward migration of southern Adriatic populations after the Last Glacial Maximum: mismatch analysis showed indeed clear signs of a rapid demographic and spatial expansion. To explain this genetic homogeneity other hypotheses were also suggested, such as adaptation to the high variability of brackish water habitats, and artificial introductions. On a Mediterranean scale, phylogenetic analyses showed the presence of five distinct geographical lineages: Aegean Sea, Greek coast of the Ionian Sea, Adriatic Sea, Tyrrhenian Sea and Southern Sicily. Analysis of molecular variance revealed a genetic partitioning mainly due to differences between groups presumably due to late Miocene geological events, while less polymorphism was present within groups and populations.